MEASUREMENT OF STUDENT SATISFACTION INDEX VALUE TO IMPROVE EDUCATION QUALITY OF RADIOLOGY IMAGING TECHNOLOGY STUDY PROGRAM UNIVERSITAS AIRLANGGA - Tyas, Rana Ayuning; Sari, Amilia Kartika; Witjaksono, Budi Priyo; Sensusiati, Anggraini Dwi; Praptono, Soegardo Indra (Journal of Vocational Health Studies, 2019)
Background: Measurement of student satisfaction index is part of internal quality assurance in education, which is nowdays becoming a main topic in higher education. At Radiologic Imaging Technology, there has been no research or data about student satisfaction index of education quality. Purpose: Therefore, this research objective was to establish student satisfaction index and analyze the factors. Method: This research was conducted with interviewing 129 student using questionnaire. Each questionnaire contains three indicators with twenty variables in total. Collected data will be counted to establish satisfaction index per indicator and in total. Result: The result of student satisfaction index per indicator were 2.93, 3.08, 3.26, which means neutral. Student satisfaction index in total was 61.65%, which means student is satisfied. Conclusion: The main factors of student satisfaction was relevance level of lesson given with the needed in internship.